Critical Discourse Analysis of President Joe Biden’s Russophobia Rhetorical Remarks Before The 77th United Nations General Assembly - Hilman Mahmud Akmal Ma'arif; Ali Maksum (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
This study investigates the extent to which President Joe Biden's speech before the 77th session of the UN General Assembly reflects US foreign policy towards Russia and Ukraine. The sample of this study was sourced from manuscripts of President Joe Biden's speeches obtained through the official US state website (www.whitehouse.com), which were then elaborated with referential sources, such as website articles, online news, and journal articles accessed via Scopus and Google Scholar. The study used Critical Discourse Analysis (CDA) to analyze President Biden's speech, delivered on September 21, 2022. The speech was transcribed and analyzed utilizing the VOS Viewer and NVivo 12 Plus applications. The findings revealed that President Biden's speech emphasized the importance of the sovereign equality principle and criticized the inconsistent use of the Veto Right by Russia and the US in the UN Security Council. The speech also discouraged Russophobia and implied a willingness to engage in diplomatic negotiations with Russia. This research contributes to the literature on US foreign policy towards Russia and Ukraine by providing a detailed analysis of President Biden's speech. The findings suggest that the US is committed to upholding the sovereign equality principle and engaging in constructive diplomacy with Russia.